MD Simulations and first principles to evaluate the role of binary Fe–V alloys layer on the radiation resistance in the alpha-iron. Issue 3 (11th February 2019) - Zhang, Meng; Ding, Xinkai; Peng, Weixiang; Zhang, Hongliang; Wu, Bingjie; Sun, Kun; Fang, Liang
ABSTRACT: Radiation damage in reactor materials caused by the collision of the fast neutrons has a great impact on the reliability and safety of nuclear reactors. The element vanadium has attracted interest in many fields due to its advantageous properties in alloys. Thus, molecular dynamics simulation (MD) and first-principles calculation have been executed here to explore the radiation-resistant properties of five materials adding a layer in the bulk (pure iron and four types of Fe–V alloys containing 10%-40% V). The following results were inferred from these simulations. Firstly, the number of Frenkel pairs (FPs) at the stable quenching stage in the bulk decreases when the Fe–V alloy is added as an anti-radiation layer to the bulk. These benefits are evident for the Fe80 V20 and alloy layers with more vanadium. The main reason is that the Fe–V binding energy is greater than the Fe-Fe binding energy, which can make the Primary Knock-On atom (PKA) lose more energy at the Fe–V alloy layer. Secondly, the average value of point-defect, cluster and defect clustered fractions in the bulk of Fe–V alloy is smaller than that in the pure iron at the stable quenching stage, especially for the Fe80 V20 alloy.